The First Year at School: An International Perspective - Tymms, Peter; Bartholo, Tiago; Howie, Sarah; Kardanova, Elena; Campelo Koslinski, Mariane; Merrell, Christine; Wildy, Helen (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book explores a largely unexplored but vital part of education: the first year at primary/elementary school. The work shows that children's progress varies enormously from school to school, class to class and child to child. This variation is important because the more progress that children make in that first year of school, the higher their academic attainment at the end of compulsory schooling. The iPIPS (international Performance Indicators in Primary Schools) project, upon which this book is based, has been able to provide deeper insights into some of the key issues within and across different contexts whilst highlighting new and some ongoing issues. Despite all the work there remain unanswered or new puzzling issues which are also explored. We need to know how to improve the education at that stage and, more broadly, we need greater clarity about when children should be taught to read and be introduced to formal arithmetic, in other words, when they should start school. The book will suggest some answers but it will raise important questions and dilemmas for which we do not, as yet, have answers. .
Dedication -- Foreword -- Part 1. History of the International Performance in Primary School Indicators project -- Chapter 1. A Reflection on Three Decades of Development -- Chapter 2. The First Year at School. A Perspective from a Personal Standpoint -- Part 2. Introduction. The Challenge of Assessing Young Children's Progress Fairly and Making Comparisons -- Chapter 3. Educational Assessment of Young Children -- Chapter 4. International Comparative Assessments in Education -- Chapter 5. International Comparative Assessments of Young Children. Debates and Methodology -- Chapter 6. Teachers' Roles in the Assessment of Young Children -- Part 3. Growth of the International Performance in Primary School Indicators -- Chapter 7. Packing 200 000 Years of Evolution in One Year of Individual Development. Developmental Constraints on Learning in the First Primary School Year -- Chapter 8. Children's Developmental Levels at the Start of School -- Chapter 9. Progress Made During the First Year at School -- Part 4. The First Year at School. Education Inequality, Poverty and Children's Cognitive Development -- Chapter 10. Measures of Family Background in the iPIPS Project - Possibilities and Limits of Comparative Studies Across Countries -- Chapter 11. The Association Between Adverse Socio-Economic Circumstances and Cognitive Development within an International Context -- Part 5. Using iPIPS Data for Teaching and Informing Policy -- Chapter 12. Strategies to enhance Pedagogical Use of iPIPS Data and to support Local Government Decision-Making in Brazil -- Chapter 13. Using Assessment Data to Inform Teaching. An Example from Lesotho -- Chapter 14. The Use of iPIPS Data for Policy Assessment, Government Evidence-Based Decision Making and Pedagogical Use by Schools in Russia -- Chapter 15. Using data to inform teaching. An example from the Western Cape, South Africa -- Chapter 16. iPIPS Research Evidence. Case Studies to Promote Data Use -- Part 6. Novel and Unexpected Findings from iPIPS -- Chapter 17. Phonological Processing and Learning Difficulties for Russian First-Graders -- Chapter 18. Name Writing Ability and its Effect on Children Future Academic Attainment -- Chapter 19. The Early Physical-Motor Development Predictors of Young Children's Mathematics Achievements -- Chapter 20. Inattentiveness Predicts Reading Achievement in Primary School, but with Hyperactivity/Impulsivity it's more Complicated -- Chapter 21. The Effects of Class Composition on First-Graders' Mathematics and Reading Results. Two Countries' Cases -- Part 7. Conclusion -- Chapter 22. Reflections and Recommendations. .
Keywords: Early childhood education; Education and state; Education; Clinical psychology; Early Childhood Education; Educational Policy and Politics; Education; Clinical Psychology